Association of the healthy eating index with overweight and obesity among children aged 4 to 9 years in the United Arab Emirates: a cross-sectional study - Cheikh Ismail, Leila; Al Dhaheri, Ayesha S.; Abbas, Nada; AbuShihab, Katia; Chokor, Fatima Al Zahraa; O’Neill, Lynda; Ali, Habiba; Mohamad, Maysm N.; Hwalla, Nahla; Nasreddine, Lara; Naja, Farah (Frontiers in Public Health, 2025)
BackgroundPediatric obesity is a growing public health concern globally and in the United Arab Emirates (UAE). Understanding diet quality in relation to obesity risk is essential for developing effective interventions. The main objective of this study is to evaluate dietary quality, as measured by the Healthy Eating Index (HEI), and examine its association with overweight and obesity among children aged 4 to 9 years in the UAE.MethodsData for this study were derived from a representative survey conducted in the three largest Emirates of the UAE: Abu Dhabi, Dubai, and Sharjah. A total of 426 children aged 4 to 9 years, recruited using a stratified cluster sampling frame, were included in the analysis. Data collection was conducted through face-to-face interviews with the main caregiver. Dietary intake was assessed via a 24-h recall. The HEI was used to examine dietary quality. Anthropometric data were collected to classify weight status using WHO BMI-for-age z-scores. Simple and multiple logistic regression models assessed associations between HEI scores and overweight/obesity.ResultsOnly 9.4% of children achieved a Moderate to Good HEI score (≥60), while 90.6% fell into the Poor category. Children with higher HEI scores had significantly lower odds of being overweight or obese (adjusted OR = 0.32, 95% CI: 0.13–0.79, p = 0.014). Key dietary gaps were identified in vegetable, whole grain, and seafood/plant protein intake. Determinants of better HEI scores included higher paternal education, while maternal employment was associated with poorer diet quality.ConclusionDiet quality among children in the UAE is generally suboptimal and is significantly associated with overweight and obesity. The HEI is a valuable tool for identifying dietary gaps and informing targeted nutritional interventions to reduce obesity risk in this population.